1005 Antibiotic-Impregnated Calcium Sulfate Beads Are Not Effective in the Primary Prevention of Infection in Open Femur and Tibia Fractures. (4th May 2021) - Fung, A; Ward, A; Patel, K; Krkovic, M
Abstract: Introduction: Infection is a major complication of open fractures. Antibiotic-impregnated calcium sulfate (AICS) beads are widely used as an adjuvant to systemic antibiotics. Whilst their efficacy in the secondary prevention of infection is established, we present the first retrospective study evaluating AICS beads in the primary prevention of infection in open fractures. Method: 214 open femur and tibia fractures in 207 patients were reviewed over a seven-year period. 148 fractures received only systemic antibiotic prophylaxis. 66 fractures also received AICS beads. The occurrence of acute infection (wound infection and acute osteomyelitis) was recorded, as well as that of long-term complications (chronic osteomyelitis, non-union and death). Results: Fractures that received AICS with systemic antibiotics had an overall acute infection rate of 42% (28/66), compared to 43% (63/148) in fractures that received only systemic antibiotics (p > 0.05). There was no significant difference in infection rate even when fractures were stratified by Gustilo-Anderson grade. There was also no significant difference in the rate of long-term complications. Conclusions: Our results indicate that the adjuvant use of AICS beads is not effective for the primary prevention of acute infection or long-term complications in open leg fractures. Further research is needed to elucidate the factors influencing the outcomes of AICS use.